2019
DOI: 10.1016/j.ygyno.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

PI3K oncogenic mutations mediate resistance to afatinib in HER2/neu overexpressing gynecological cancers

Abstract: Objective: Aberrant expression of HER2/neu and PIK3CA gene products secondary to amplification/mutations are common in high-grade-serous-endometrial (USC) and ovarian-cancers (HGSOC). Because scant information is currently available in the literature on the potential negative effect of PIK3CA mutations on the activity of afatinib, in this study we evaluate for the first time the role of oncogenic PIK3CA mutations as a potential mechanism of resistance to afatinib in HGSOC and USC overexpressing HER2/neu. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Another study described the progression of disease on trastuzumab with paclitaxel in three women with HER2+ recurrent high-risk histology tumors including two serous and one endometrioid [86]. In vitro experiments in cells that overexpress ERBB2 showed that oncogenic mutations in PI3K resulted in resistance to afatinib, a tyrosine kinase inhibitor that inhibits ErbB signaling [87]. A randomized trial of systemic chemotherapy (carboplatin and paclitaxel) with trastuzumab in serous carcinomas increased median progression-free survival from 8.0 months to 12.6 months.…”
Section: Treatmentmentioning
confidence: 99%
“…Another study described the progression of disease on trastuzumab with paclitaxel in three women with HER2+ recurrent high-risk histology tumors including two serous and one endometrioid [86]. In vitro experiments in cells that overexpress ERBB2 showed that oncogenic mutations in PI3K resulted in resistance to afatinib, a tyrosine kinase inhibitor that inhibits ErbB signaling [87]. A randomized trial of systemic chemotherapy (carboplatin and paclitaxel) with trastuzumab in serous carcinomas increased median progression-free survival from 8.0 months to 12.6 months.…”
Section: Treatmentmentioning
confidence: 99%
“…As AKT is directly phosphorylated by PIK3CA ( 41 ) and mTOR is a known downstream target of the ERBB2-PIK3CA-AKT axis ( 42 ), the expression levels of AKT phosphorylation (p-AKT/AKT) and mTOR phosphorylation (p-mTOR/mTOR) were assessed as indicators of PIK3CA activity. siERBB2 cells expressed significantly lower AKT and mTOR phosphorylation levels compared with siCtrl cells, while ERBB2 vec cells expressed significantly higher AKT and mTOR phosphorylation levels compared with Ctrl vec cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The combination prevented resistance in preclinical USC models, and led to substantial cancer regression in large xenografts, previously resistant to single-agent PIK3CA or pan-Her inhibition. These preclinical results suggest that combination regimens using highly targeted drugs may be of great benefit while synergistic combinations could induce more durable clinical responses in USC [ 56 , 57 , 58 , 59 ].…”
Section: Immunotherapy and Tumor-draining Lymph Nodesmentioning
confidence: 99%